GOOGLE MEET SEBAGAI MEDIA PEMBELAJARAN DARING OLAHRAGA DI SMA MUHAMMADIYAH 2 SURAKARTA - Puji Wibowo; Ardian Ajrun Pangestu; Agam Akhmad Syaukani (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
One of the important and crucial human needs to be fulfilled is education. This is because in education a process will be formed so that humans have the ability and maturity in terms of academics and psychology as well as to recognize potential which is then developed as a passion. The existence Covid-19 had consequences to impact the activities involving various fields of life, one of which is the field of education where teaching and learning activities must transform from face-to-face learning to online or virtual learning. In this case teachers and students and even parents have to adapt to this online learning system. Departing from this, teachers are certainly required to take advantage of existing technology to strive for teaching and learning activities to continue even though virtually. A teacher must use media that can help carry out online learning, for example media in the form of a web based on Google Meet. The purpose of this research was to find out how to use Google Meet as an online learning media, especially in Sports Subjects at SMA Muhammadiyah 2 Surakarta. This study used a qualitative descriptive method. The use of Google Meet in the Sports subject at SMA Muhammadiyah 2 Surakarta has a good role in assisting the implementation of online learning.